Serum Nonenzymatic Anti-Oxidants in Nigerian Children with Severe Pneumonia: Association with Complications and Hospital Outcomes - Bankole Peter Kuti; Oyeku Akibu Oyelami (Pediatric Respirology and Critical Care Medicine)
Background: Tissue damaging effects of free radicals generated during the acute inflammation processes of childhood pneumonia may be ameliorated by antioxidants. This study aimed to determine the serum non-enzymatic antioxidants {Total Phenols, Carotenoids, Flavoids, Ascorbic acid, Tocopherols and Total Antioxidant Contents (TAC)} of Nigerian children with or without severe pneumonia (SP) and relate these to the presence of parapneumonic effusions (PPE) and length of hospitalisation (LOH). Methods: Consecutive children two months to 14 years admitted with severe pneumonia and their age and sex matched controls were recruited over a 12-month period at a Nigerian Health facility. Serum antioxidants were assayed using chromatography method and related to PPE and LOH. Results: The majority (86.1%) of the 144 children (72 each with SP and controls) were under-fives and eight (11.1%) of SP group had PPE. Median (IQR) LOH was 5.0 (4.0 – 7.0) days and 45 (62.5%) had prolonged (≥5 days) hospital stay with 3 (4.2%) mortality. Serum Tocopherols, 10.1 (4.7) vs. 13.2 (7.6) µg/dl; total flavoids 1.0 (0.6) vs. 1.3 (0.8) µg/dl and TAC 6.1 (4.4-8.9) vs. 7.4 (5.0 – 13.3) ng/dl were significantly lower in children with SP (p < 0.05). Serum antioxidants levels were not related to the PPE, however children with prolonged LOH had lower TAC (p<0.05), which also correlated negatively with LOH (r =- 0.418; p < 0.001) Conclusion: Lower serum antioxidants observed in children with severe pneumonia may connote increased demand or increased predisposition to the infection. Antioxidant supplementation may aid recovery of Nigerian children with SP.